PHYSICO-CHEMICAL BASIS OF OBTAINING DOUBLE SUPERPHOSPHATE FROM KARATOG PHOSPHORITE (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the physical-chemical processes involved in the production of Brown Superphosphate from Karatog phosphorite, an essential step in fertilizer manufacturing. The study delves into the acidulation and solubilization methods, presenting results and a comprehensive discussion on the efficacy of the process.